The Techne of Nutrition in Ancient Greek Philosophy - Preus, Anthony (Revista Archai, 2020)
The preparation of food and nutrition is a pervasive techne in the classical Greek world. Indeed, food technology may be a defining characteristic of humanity (Levi-Strauss, 1964). We begin with a glimpse of a tension in the use of the word techne in relation to the preparation of food in Plato’s Gorgias 462d-e. Turning to the Presocratics, we discern three distinct perspectives on food, those of Empedocles, Anaxagoras, and the treatise Regimen (Î ÎµÏá½¶ Î”Î¹Î±Î¯Ï„Î·Ï‚). In Regimen, we find an anticipation of the distinctions made by Plato in the Gorgias passage, and trace some of the implications in what we may call the “food technology” of this treatise that manages to be both philosophical and technically informative.